Syntactic Generation of Research Thesis Sketches Across Disciplines Using Formal Grammars - Ismail Babajide Adewumi; Abejide Ade-Ibijola (Journal of Information System and Informatics, 2023)
A part of the prerequisites for granting a degree in higher education institutions, students at postgraduate levels normally carry out research, which they do report in the form of theses or dissertations. Study has shown that students tend to go through difficulties in writing research thesis across all disciplines because they do not fully comprehend what constitutes a research thesis. This project proposes the syntactic generation of research thesis sketches across disciplines using formal grammars. Sketching is a synthesis technique which enables users to deliver high-level intuitions into a synthesis snag while leaving low-level details to synthesis tools. This work extends sketching to document generation for research thesis documents. Context-free grammar rules were designed and implemented for this task. A link to 10,000 generated thesis sketches was presented.